Moral Responsibility While Dreaming - Robert Cowan (Ergo, An Open Access Journal of Philosophy)
Are subjects ever morally responsible for their dreams? In this paper I argue that if, as some theories of dreams entail, dreaming subjects sometimes express agency while they dream, then they are sometimes morally responsible for what they do and are potentially worthy of praise and blame while they dream and after they have awoken. I end by noting the practical and theoretical implications of my argument.